Manajemen Stres Kerja Pengusaha Untuk Meningkatkan Kinerja Perusahaan Di Industri Batik Laweyan Surakarta - lukman hakim; Eko Sugiyanto (Benefit: Jurnal Manajemen dan Bisnis, 2017)
This study aims to: (1) Identifying the causes of workplace stress occurring entrepreneurs in the batik industry Laweyan Surakarta Central Java. (2) Identify the effect or impact stress businessman working in the batik industry Laweyan Surakarta Central Java. (3) Develop a model of handling work stress entrepreneurs in the batik industry Laweyan Surakarta Central Java. This research uses descriptive method with a "Case Study". The case study is an in-depth study of the individual, a group, an organization, a program of activities, and so within a specified time. In this study aim to obtain a complete and profound description of a job stress entrepreneur. This case study produced data for further analyzed to produce a workable theory for batik entrepreneurs in solving the problems of job stress entrepreneur. The study concluded there are two characteristics of job stress, organizational dynamics work stress and group dynamics work stress. While handling through two approaches, namely causation and development analysis. The analytical approach development through: (1) analysis of the role, (2) create a culture of superior organization, and (3) establishment or consultation center changes, (4) institutional program and (5) a spiritual program